THROUGHPUT IN MACRO-CELLULAR AND MICRO-CELLULAR RADIO SYSTEMS WITH MULTIPLE CORRELATED LOG-NORMAL INTERFERERS - SAFAK, A; SAFAK, M (I E E E, 1994)
[Abstract Not Available]
44th Vehicular Technology Conference: Creating Tomorrows Mobile Systems (VTC 1994) -- JUN 08-10, 1994 -- STOCKHOLM, SWEDEN